(untitled) (Medical Forum Monthly, 2024)
Background: Helicobacter pylori produce gastric inflammation and interfere with iron by producing extragastric complications. The deficiency of iron in patients with gastritis or peptic ulcer leads to iron deficiency anemia. Objective: The objective of this study was to elucidate the effects of Helicobacter pylori infection on red serum iron and ferritin levels. Study Design: Cross sectional analytical study Place and Duration of Study: This study was a conducted at the University of Health Sciences, Lahore from March 2009 to September 2009. Materials and Methods: A total number of 90 subjects were included in the study. They were divided into group A (30 subjects with gastric symptoms and H. pylori infection), group B (30 subjects with gastric symptoms but without H. pylori infection), and group C (30 normal healthy age and sex matched subjects). H. pylori infection was considered positive on the basis of positive serology, rapid urease test and histopathological examination. Serum ferritin was estimated by chemilumisecne technique while serum iron was measured by endpoint colorimetric method. Results: The results of this study did not show any significant effect on serum ferritin and serum iron (p value > 0.05) within the individual groups nor when compared with each other. Conclusion: H. pylori infection did not affect the serum ferritin and serum iron levels